The Influence of Aerosols and Meteorological Conditions on the Total Rain Volume of the Mesoscale Convective Systems Over Tropical Continents - Sudip Chakraborty; Rong Fu; Daniel Rosenfeld; Steven T. Massie (Geophysical Research Letters)
Abstract This study provides an observational assessment of the variations of the total rain volume (TRV) with aerosols through the entire lifetime of mesoscale convective systems (MCSs) over tropics. Using 70,000 MCSs' samples, we show that TRV increases with aerosols from clean to moderately heavy polluted conditions (aerosol optical depth [AOD] ~ 0.0–0.4). TRV decreases when AOD exceeds 0.5. The TRV change with AOD is strongest under favorable meteorological conditions, such as high total precipitable water (45–75 kg/m2), high convective available potential energy (1,200–2,400 J/kg), and intermediate vertical wind shear (9–21 × 10−4/s). TRV of MCSs increases from 2 to 4 km3 (rain depth ~ 20–40 mm) when AOD < 0.15 or >0.5, to more than 12 km3 (~120 mm) when 0.2 < AOD < 0.4 under above the mentioned optimal meteorological conditions. The basic response of TRV to aerosol concentrations is similar under all the meteorological conditions and during all stages of the MCS lifecycle.